Consequences of Child Abuse in India and Around the World: Exploring the Widespread Impact of Child Abuse on Individuals and Society (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Child Abuse in India and around the world is common with traumatic post child abuse consequences. Some of the consequences post child abuse includes issues with the following growth stages developmental, psychological, mental, anti-social behaviors and many more. It is necessary to educate the Parents and Guardians of the effects of Child Abuse so it is no longer a norm in many countries around the world.